Study of Package and Value Added of Patchouli Oil Refining Business in Kabangka District, Muna Regency - Uliana, Wa; Rianda, La; Syukri, Muhammad (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2020)
ThisÂ study aims to: (1) determine the added value of the patchouli oil refining business; (2) find out the added value of the patchouli oil refining business. Data were processed using qualitative analysis to determine the pattern of marketing channels while determining the amount of added value obtained by patchouli oil processing businesses using the Hayami method. The population in this study are all businesses of patchouli oil refining owners. The added value obtained by the essential oil refining business in Kabangka District of Muna Regency is Rp.4,607/kg meaning that every 1 kg of patchouli raw material will produce output in the form of essential oil of Rp. 4,607 per production process and the ratio of value-added to the output value is 41,73 with the understanding that every kg of patchouli which is processed into essential oils will get an added value of 39,16 %. The pattern of marketing channels, namely patchouli oil refining business-patchouli oil traders in large-traders village.Â